Large Thrombotic Coronary Artery Aneurysm Treated With a Covered Stent Using OCT for Procedural Guidance - Georgina Fuertes Ferre; Galache Osuna JG; Diarte de Miguel JA; Sánchez Rubio J (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
Coronary artery aneurysm (CAA) is an uncommon finding in patients undergoing a coronary angiography, with an incidence of less than 5% [1]. CAA is defined as coronary dilation of more than 1,5 times the adjacent vessel diameter. The majority of CAA in adults are of an atherosclerotic origin [2]. Treatment of CAA remains challenging. In the past years surgery was the only successful approach of symptomatic CAA associated with coronary artery stenosis. Lately a less aggressive strategy has emerged with the inclusion of covered stents (CS). However the number of reported cases of CS in the treatment of CAA is low.